Existentialist Freedom, Distorted Normativity, and Emancipation - Sorin Baiasu (Oñati Socio-Legal Series)
Usually associated with a view of freedom as absolute, Sartre’s philosophy seems particularly able to account for the indeterminacy that we experience today in most areas of human experience that have a normative dimension. Without denying that this is a plausible reading, it will be argued here that it is nevertheless a problematic interpretation. On this reading, existentialism seems unable to account for the fact that we are powerfully conditioned by a significant number of factors, which limit our freedom and, in certain situations, make emancipation a normative requirement. It is held here that this problem can be addressed and a less problematic interpretation of Sartre can be defended, once we start to acknowledge that in Sartre we have a variety of notions of freedom that can provide a robust account of our freedom, of authentic choice and of responsibility.